Coat fibres of Nigerian sheep and goats: A preliminary characterisation - Hall, S.J.G.; Russel, A.J.F.; Redden, H. (Elsevier, 1996)
Samples of fibre were taken from sheep (n = 45) and goats (n = 24) of the West African Dwarf (WAD) and northern breeds in Nigeria. Three types of coat were noted in sheep: fine woolled, double coated and predominantly hairy. Median fibre diameters were 14.9, 75.7 and 93.3 µm, respectively. Goats tended to have more unimodal coats with median fibre diameters of individuals between 36.4 and 128.4 µm. In general, smaller bodied sheep and goats had finer and less variable coats. In neither species did coat type depend on breed. Particularly in the WAD goat, which with the WAD sheep inhabits the humid south, the observed fibre diameter distributions could suggest a reduction of primary follicles. As these follicles are associated with sweat and sebaceous glands, while secondary follicles are associated with sebaceous glands only, it is possible that the coat type may be a consequence of evolution away from the use of sweating to cool the body.